Association of liver function tests with severity of disease in patients with COVID-19 - Ipek, Serkan; Gelgec, Sule Ayse; Turker, Gamze; Aydin Catakli, Serra (International Journal of Research in Medical Sciences, 2024)
Background: We aimed to investigate the association of liver function tests with disease severity at admission and during hospitalization in patients with coronavirus disease 2019 (COVID-19). Methods: Blood tests of patients who were hospitalized due to COVID-19 were retrospectively analyzed. Liver tests included serum aspartate aminotransferase, alanine aminotransferase, gamma-glutamyl transferase, total bilirubin, and albumin. Besides these, C-reactive protein and ferritin were also analyzed in the study. Levels of these tests at admission and peak levels during hospitalization were then recorded. Severe COVID-19 infection was defined as the reason for ICU admission. Both the associations of the levels of liver tests at admission and peak levels during hospitalization with severe disease were evaluated. Results: The study included a total of 602 patients, and 127 (21.1%) of the patients were hospitalized in the ICU. In our study, only albumin level abnormality was significantly associated with severe disease in COVID-19 patients at admission. However, during hospitalization, a significant association was found between severe disease and abnormal AST, ALT, GGT, T.BIL, albumin, and ferritin levels. During hospitalization, it was also observed that the rates of severe disease cases increased as AST, ALT, GGT, and T.BIL levels increased. Conclusions: Abnormal liver function tests may be a predictor for severe disease in patients with COVID-19. It is therefore important to monitor liver function tests in hospitalized patients.